The Rationality of Antibiotics Use on Inpatient Department of Pediatric in One of the Hospital in Cimahi - Vina Septiani; Pudjiastuti Kartidjo; Fenny Asri Nurdiani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The purpose of this study is to assess the rationality of the use of antibiotics from inpatients in one hospital in Cimahi, West Java. The research about rationality analysis of antibiotics at pediatric inpatient in one of the hospitals in Cimahi was done retrospectively use descriptive analysis design. The data source was the medical record of a patient who treated at the children's inpatient ward from January through March 2017. The result shows that 39% of infected patients were children under one-year-old. Three significant cases of diseases that occurred in the period were bronchopneumonia, typhoid fever, and typhoid fever+bronchopneumonia. Antibiotics therapy was given as single therapy as well as combination, where cefotaxime (51%) and ceftriaxone (42%) were the most antibiotics widely used as single therapy. Antibiotic use at children inpatient ward during the period January – March 2017 on bronchopneumonia, typhoid fever, and typhoid fever + bronchopneumonia patients was not 100% rational referring to criteria: correct diagnosis, correct indication, the correct drug of choice, correct dosage, correct method, and correct time interval of drug administration.